Critical Thinking Improvement through Numeracy Literacy: Insights from Senior High School Practices - Arum Afdhalishani Jannati; Sutama Sutama; Nining Setyaningsih; Mazlini Adnan (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Numeracy literacy skills are the main focus in the Indonesian education system to prepare students for the 21st century. However, in practice, efforts to acculturate numeracy literacy in schools are still not implemented optimally. Therefore, this study has two main objectives, namely: 1) to describe the acculturation of numeracy literacy of senior high school students; 2) to explore the critical thinking disposition of senior high school students. This research is part of a developmental research that focuses on a qualitative approach with an ethnographic design. The subjects in this study were students, subject teachers, and one of the senior high schools in Surakarta. The research data were collected through interviews conducted with teachers, direct observation during classroom learning activities, and documentation related to mathematics assessments used in schools. Data validation was conducted using source triangulation technique to ensure data credibility.